2002
DOI: 10.1081/pfc-120004476
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, Desorption, and Mobility of Two Insecticides in Malaysian Agricultural Soils

Abstract: Laboratory studies utilizing radioisotopic techniques were conducted to determine the adsorption, desorption, and mobility of endosulfan (6,7,8,9,10,10-hexachloro-1,5,5a,6,9,9a-hexahydro-6,9-methano-2,4,3-benzodioxanthiepin3-oxide) and methamidophos (O,S-dimethyl phosphorothioate) in sandy loam and clay soils of the Cameron Highlands and the Muda rice-growing area, respectively. High Freundlich adsorption distribution coefficients [Kads(f)] for endosulfan (6.74 and 18.75) and low values for methamidophos (0.40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
5
16
0
Order By: Relevance
“…Vagi et al (2010) have reported that organic matter as well as other soil properties played a role in adsorption of dimethoate on various Greek soils having OM varying from 1.0 to 4.2%. Data from other previous studies indicate a good correlation between K f and OM for the organophosphate pesticides in soils having OM<1.0%; the higher the organic matter, the larger the K f value (Garg et al, 2008;Islam et al, 2010;Ismail et al, 2002). The K f and EC values were also positively correlated (R 2 >0.67).…”
Section: Resultssupporting
confidence: 56%
“…Vagi et al (2010) have reported that organic matter as well as other soil properties played a role in adsorption of dimethoate on various Greek soils having OM varying from 1.0 to 4.2%. Data from other previous studies indicate a good correlation between K f and OM for the organophosphate pesticides in soils having OM<1.0%; the higher the organic matter, the larger the K f value (Garg et al, 2008;Islam et al, 2010;Ismail et al, 2002). The K f and EC values were also positively correlated (R 2 >0.67).…”
Section: Resultssupporting
confidence: 56%
“…Adsorption-desorption studies of pesticides such as metsulfuron-methyl, chlorpyrifos, fenvelerate, 2,4-D and paraquat (Cheah et al, 1997;Ismail and Maznah, 2006;Mehdi et al, 2009;Ismail and Ooi, 2012) have been reported. Although many studies on the adsorption/desorption of pesticides have been published, there is still lack of information on the adsorption-desorption behavior of thiram in soil, especially Malaysian soils.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption-desorption isotherms are usually described by linear models and/or Freundlich models. It has been shown that sorption-desorption capacity of pesticides in soils depend on the type of soil, temperature, pH and properties of pesticide itself (Ismail and Maznah, 2006;Cao et al, 2008;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Sharma et al (2013) and Singh (2002) have shown that the adsorption of hexaconazole is correlated to soil organic matter content. Generally, adsorption of pesticides is positively correlated to organic matter, clay content, and CEC values of the soil (Liu et al 2010, Ismail and Maznah 2006, Arias-Estevez et al 2006.…”
Section: Adsorption-desorption Studiesmentioning
confidence: 99%